Curriculum Development Models - Hanafiah Hanafiah; Dudung Ali Nurdin; Tuti Nursafitri (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to explore the concept of curriculum development in schools. This research, sometimes referred to as a type of library research, involves research or obtaining materials from various sources such as magazines, books, articles, and others that are relevant to the problem to be solved. The output of this research is curriculum development, namely the process of curriculum planning and design by curriculum developers, and the activities carried out so that it becomes teaching materials and reference materials to achieve national education goals. In designing the curriculum, teachers can choose from several models including: Administrative Model, Grass Roots Approach Model, Demonstration Model, Beauchamp Model, Roger's Model, Problem Solving Model, and Taba's Inverted Model. curriculum development includes curriculum planning, curriculum organization, staffing and curriculum control. Successful curriculum implementation results from careful planning and attention to two important things, namely communicating the implementation plan and the support of all resources in the implementation.